Neurovascular damage in experimental allergic encephalomyelitis: a target for pharmacological control - C. Bolton (Mediators of Inflammation)
The blood-brain barrier (BBB) is composed of a continuous endothelial layer with pericytes and astrocytes in close proximity to offer homeostatic control to the neurovasculature. The human demyelinating disease multiple sclerosis and the animal counterpart experimental allergic encephalomyelitis (EAE) are characterized by enhanced permeability of the BBB facilitating oedema formation and recruitment of systemically derived inflammatory-type cells into target tissues to mediate eventual myelin loss and neuronal dysfunction. EAE is considered a useful model for examining the pathology which culminates in loss of BBB integrity and the disease is now proving valuable in assessing compounds for efficacy in limiting damage at neurovascular sites. The precise mechanisms culminating in EAE-induced BBB breakdown are unclear although several potentially disruptive mediators have been implicated and have been previously identified as potent effectors of cerebrovascular damage in non-disease related conditions of the central nervous system. The review considers evidence that common mechanisms may mediate cerebrovascular permeability changes irrespective of the initial insult and discusses therapeutic approaches for the control of BBB leakage in the demyelinating diseases.